New application of chemokine receptor CCR6 inhibitor in prevention of psoriasis recurrence - QIN HUI; XUE FENG; CHEN LIHONG; ZHENG JIE; LIU NA; WANG XIAOPAN; KWON SUNG; ZHANG LI; LI XIA; WANG LANQI (2023)
The invention provides a novel application of a chemokine receptor CCR6 inhibitor in prevention of psoriasis recurrence. Specifically, the invention provides an application of a chemokine receptor CCR6 inhibitor, the chemokine receptor CCR6 inhibitor is used for preparing a preparation or a composition, and the preparation or the composition is applied to a subject so as to prevent relapse of psoriasis in the subject. The invention further provides a medicine product for preventing relapse of psoriasis. The relapse of psoriasis can be effectively prevented or relieved by using the medicine product provided by the invention. 本发明提供了趋化因子受体CCR6抑制剂在预防银屑病复发中的新应用。具体地，本发明提供了一种趋化因子受体CCR6抑制剂的用途，用于制备一制剂或组合物，所述制剂或组合物被施用于一对象，以防止所述对象中银屑病的复发。本发明还提供了一种防止银屑病复发的药物产品。使用本发明所提供的药物产品可以有效预防或缓解银屑病的复发。